A Reading Teacher’s Perspective in Constructing the Students' Critical Thinking - Angraini, Desti; Putra, Wahyu; Masurai, Puti; Wahyudi, Luthfi; Firman (SALEE: Study of Applied Linguistics and English Education, 2024)
In this research, a descriptive qualitative design was employed to delve into the perspectives of reading teachers concerning the cultivation of students' critical thinking skills. Through in-depth interviews, the research aimed to unravel the specific methods and instructional techniques these teachers utilized to nurture critical thinking in their students. The research emphasized an open-ended interview process, allowing for a nuanced exploration of the strategies employed by experienced teachers, with a focus on those possessing over 10 years of teaching expertise. The findings revealed that reading teachers, according to the constructivist principles outlined by Brooks and Brooks (2005), acted as facilitators, empowering students to independently construct their understanding of content. The constructivist approach emphasized autonomy, hands-on experiences, and cognitive language use in assignments. Teachers adapted lessons based on student responses, encouraged dialogue, inquired about students' understandings before presenting their own, and fostered experiences that challenged initial hypotheses. Despite challenges posed by standardized testing and ingrained educational approaches, constructivist principles proved effective in cultivating critical thinking skills. The research contributed valuable insights into the complex dynamics of critical thinking in reading instruction, advocating for student-centric and constructivist approaches in education. Keywords: Reading teachers’ perspective: students, critical thinking